LANGUAGE BARRIERS AND ASSESSMENT VALIDITY IN MOROCCAN SCIENCE CLASSROOMS: EVIDENCE FROM DIAGNOSTIC TESTING - Zineb Labbar; Abdellatif El Moudni (PUPIL: International Journal of Teaching, Education and Learning, 2025)
While Arabic is still the primary language of instruction and comprehension in Moroccan public schools, teachers frequently use French to evaluate their students. This study investigates the effects of language barriers on students' performance and the reliability of science tests. A sample of secondary students was given a diagnostic test in two different formats: (1) a bilingual version with Arabic translations of important terms and instructions, and (2) a French-only version. Examining the relationship between linguistic accessibility and test comprehension, response accuracy, and overall achievement scores was the goal. According to preliminary findings, students perform better when given Arabic translations, which raises the possibility that linguistic considerations rather than subject-matter expertise could account for some of the low achievement in science courses. Correlations between test versions, item difficulty, and student language background will be further investigated through data analysis. By emphasizing the significance of language-inclusive testing policies in Morocco and comparable educational systems, this study seeks to inform fair assessment practices in multilingual contexts. By emphasizing the significance of language-inclusive testing policies in Morocco and comparable educational systems, this study seeks to inform fair assessment practices in multilingual contexts.